Ulkus Diabetikum Pedis Dextra: Laporan Kasus - Lensy Khosinatus Syarifah; Nugroho Budi Santoso; Linda Armelia (Jurnal Impresi Indonesia, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease with increased blood glucose levels due to impaired insulin secretion or work. According to the International Diabetes Federation (2021), there are around 537 million people with DM in the world, and the number continues to rise. One of the serious complications is diabetic foot ulcers, which are chronic lesions on the feet due to peripheral neuropathy, ischemia, and infection. This paper discusses the case of a 47-year-old woman with a diabetic ulcer after being hit by a motorcycle exhaust. The wound is enlarged, purulent, swollen, and accompanied by severe pain. 7-year history of DM with Blood Sugar At 632 mg/dL and HbA1C 13.6%. Management includes antibiotics, insulin drip, insulin sliding scale, and debridement when blood sugar is <200 mg/dL. Diabetic foot ulcers arise as a result of a combination of neuropathy, ischemia, and infections exacerbated by chronic hyperglycemia. Minor wounds can become severe infections when glucose control is poor. Assessment of severity uses Wagner's classification and degree of infection to determine therapy. Treatment requires a multidisciplinary approach, including blood sugar control, antibiotic therapy, wound care, and debridement. Prevention through education, glucose control, and regular foot care is important to reduce the risk of complications and amputations.